(untitled) (Mongolian Journal of Agricultural Sciences, 2025)
A total of 18 bacterial strains were isolated from the root nodules of Chesniella macrantha Cheng f. ex H.C.Fu, a very rare, subendemic, and relict plant species in Mongolia. Based on 16S rRNA gene sequence analysis, the strains were assigned to four genera: Priestia (10 strains), Rhizobium (6 strains), Peribacillus (1 strain), and Neobacillus (1 strain). Ten strains exhibited 99.65–100% similarity to Priestia aryabhattai B8W22T or Priestia megaterium NBRC 15308T, while strains Gr2-1, Gr2-2, Gr2-3-1, Gr3-1, Gr3-2-1, and UN2-3 showed 99.78–100% similarity to Rhizobium mongolense subsp. mongolense USDA 1844T. Two strains, Gr2-4-1 and UN1-2, were most closely related to Peribacillus simplex NBRC 15720T (99.93–100%) and Neobacillus drentensis LMG 21831T (99.71%), respectively. Eight strains produced indole-3-acetic acid (IAA) in LB medium supplemented with 5 mM L-tryptophan, and three exhibited phosphate solubilization activity. Six Priestia strains, Gr2-3, Gr2-4-2, Gr3-2, Gr3-3, Gr3-3-1, and UN1-3, showed high IAA production, whereas Priestia strains Gr2-3, Gr3-3, and UN2-5 solubilized phosphate on Pikovskaya’s agar, with a solubilization index (SI) of 2.16 ± 0.02 cm. Among all isolates, Rhizobium strain Gr3-2-1 was the most effective in promoting both root elongation and branching in C. macrantha plantlets, indicating its potential use in propagation and conservation of this endangered Mongolian legume.